Risk Identification And Analysis In Engineering, Procurement, And Construction (EPC) Projects At Mining Facilities By PT. XYZ - Syakieb Alkatiri, Mushab; Sagita Riantini, Leni; Okto Bangkit Sentosa, Bastian (Publisher Cv. Inara, 2025)
Risk management in Engineering, Procurement, and Construction (EPC) projects within the mining sector is critical to ensure project success and avoid potential disruptions. PT. XYZ, a company engaged in mining infrastructure development, faces a variety of risks ranging from technical and logistical challenges to external and environmental uncertainties. This study aims to identify and analyze the risks present in EPC projects carried out by PT. XYZ. The research begins with risk identification through expert interviews and document analysis, followed by a qualitative risk analysis based on the Project Management Body of Knowledge (PMBOK) framework to assess the probability and impact of each risk. The findings reveal several high-priority risk factors that require focused attention in future project planning. This study is expected to provide valuable insights into risk conditions in EPC projects and contribute to better risk-informed decision-making processes for PT. XYZ.